Pengaruh Harga Dan Promosi Terhadap Keputusan Pembelian Melalui Kepuasan Konsumen : Studi Pada Toko Kelontong Src Tawangmangu - Utari Trivena; Fransius Awaldo Damanik (Jurnal Minfo Polgan, 2026)
This study aims to examine the effect of price and promotion on purchasing decisions, with customer satisfaction serving as a mediating variable, at SRC Tawangmangu Store. This research employs a descriptive quantitative approach using a purposive sampling technique. The sample consists of 160 customers of SRC Tawangmangu Store. Data were collected through questionnaires and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM–PLS) method with the assistance of SmartPLS software. The findings reveal that price and promotion have a positive and significant effect on both customer satisfaction and purchasing decisions. Customer satisfaction also has a positive and significant effect on purchasing decisions and partially mediates the relationship between price and promotion and purchasing decisions. Among the variables examined, price has the most dominant influence on purchasing decisions. Therefore, appropriate pricing strategies and effective promotional activities play a crucial role in enhancing customer satisfaction and encouraging purchasing decisions at SRC Tawangmangu Store.